2020
DOI: 10.1111/cas.14701
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 and oncogenic Ras constitute a regulatory switch for stimulus‐dependent E‐cadherin downregulation

Abstract: E-cadherin, encoded by the CDH1 gene, is a calcium-dependent cell adhesion molecule localized in adherens junctions of epithelial cells. 1 The downregulation of E-cadherin expression is considered one of the hallmarks of cells undergoing epithelial-mesenchymal transition (EMT) and is closely associated with cell invasion. It has been reported that interference of E-cadherin function by neutralizing antibodies results in the acquirement of invasive properties by nontransformed epithelial cells. 2 Moreover, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(102 reference statements)
0
4
0
1
Order By: Relevance
“…Studies have shown that E-cadherin is a key molecule to maintain the adhesion between cancer cells [36][37][38]. Inhibiting the expression of E-cadherin can reduce the adhesion between cancer cells and lead to the shedding of cancer cells from primary cancer tissue, which induces the metastasis of colon cancer [39,40]. In addition, MMP-9 can degrade E-cadherin, subsequently reduce the adhesion between cancer cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that E-cadherin is a key molecule to maintain the adhesion between cancer cells [36][37][38]. Inhibiting the expression of E-cadherin can reduce the adhesion between cancer cells and lead to the shedding of cancer cells from primary cancer tissue, which induces the metastasis of colon cancer [39,40]. In addition, MMP-9 can degrade E-cadherin, subsequently reduce the adhesion between cancer cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The let-7 family has been found to be involved in the promotion of EMT in endometrial carcinosarcomas [85]. The action of miR-141 and miR-200 is thought to be based on the regulation of ZEB1/ZEB2 expression involved in the regulation of E-cadherin expression [86][87][88]. Let-7 is thought to regulate the expression of the high mobility group AT-hook 2 (HMGA2), an embryonic nuclear factor [85], which in turn regulates the expression of Snail, Slug, ZEB1, and ZEB2 inducing EMT [89].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Let-7 is thought to regulate the expression of the high mobility group AT-hook 2 (HMGA2), an embryonic nuclear factor [85], which in turn regulates the expression of Snail, Slug, ZEB1, and ZEB2 inducing EMT [89]. miR-34b Down-regulated [90] miR-101 Down-regulated [90] miR-106 Promotion of EMT [91] Up-regulated [91] miR-133 Up-regulated by progesterone [31] Promotion of EMT [84]; promotion of endometrial epithelial cell proliferation [31] Down-regulated [90] miR-141 Promotion of EMT [84]; regulation of ZEB1/ZEB2 expression [86][87][88] Up-regulated [84,90] miR-144 Promotion of EMT [91] Up-regulated [91] miR-152 Up-regulated by progesterone [48] regulation of GLUT3 expression [48] Down-regulated [90] miR-200 Promotion of EMT [84]; regulation of ZEB1/ZEB2 expression [86][87][88] Up-regulated [84] miR-203 Up-regulated in secretory phase and in implantation window [32] Promotion of EMT [84] Up-regulated [84] miR-205 Promotion of EMT [84] Up-regulated [84,90] miR-224 Promotion of EMT [84] Down-regulated [84] miR-411 Down-regulated [90] miR-429 down-regulated during implantation in mouse [45] Promotion of EMT [84] Up-regulated [84] Analysis of endometrial serous adenocarcinoma showed an up-regulation of miR-205 and down-regulation of miR-10b, miR-29b,...…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Consequently, loss of E-cadherin promotes the transformation of stationary epithelial cells to a migratory mesenchymal phenotype through a cascade process involving several intermediate E/M phenotypes. Apart from mutation, loss of E-cadherin may also be orchestrated by downregulation due to epigenetic or transcriptional silencing ( 12 , 13 ). All the same, mesenchymal markers such as vimentin, N-cadherin, fibronectins, smooth muscle actin, and matrix metalloproteases (MMP) also become upregulated and function concurrently with the loss of E-cadherin during the EMT program ( 14 ) ( Figure 1 ).…”
Section: Emt and Metastasismentioning
confidence: 99%